Application of K-Means Cluster and Spatial Statistics using Python to Analyze the Indicators of Indonesia Information Technology - Suharjo, Bambang (Publisher: Fakultas Ilmu Komputer, Institution: Universitas Lancang Kuning, 2021)
The use of computers and the internet is very important for business improvement. Analysis of its use for delineation and development plans in order to provide a better role in the business field. The problem is that there is no information technology literacy map in Indonesia that can provide an overview for national policy formulation. The research was carried out to compile a map of mastery of information technology in Indonesia by data mining from the Central Bureau of Statistics and analyzed it into 4 clusters of mastery of information technology. The presentation results in the form of a spatial statistical map showing the mastery of information technology makes it easier for executive decisions to be made, which can be followed up with education, socialization and other floating plans to increase indications of mastery of information technology to increase business success.